Stress-modulated relaxor-to-ferroelectric transition in lead-free (Na1/2Bi1/2) TiO3-BaTiO3 ferroelectrics - Schader, Florian H.; Wang, Zhiyang; Hinterstein, Manuel; Daniels, John E.; Webber, Kyle Grant (Physical Review B, 2016)
The effect of external mechanical fields on relaxor 0.94(Na1/2Bi1/2) TiO3-0.06BaTiO(3) was investigated by means of temperature-and stress-dependent dielectric constant measurements between 223 and 673 K. Analogous to previous investigations that showed an electric-field-induced ferroelectric long-range order in relaxor ferroelectrics, we show that compressive stress can also result in the transition to the long-range ferroelectric order, marked by the formation of an anomaly in the permittivity-temperature curves and a nonlinear, remanent change in permittivity during mechanical loading. In situ stress-dependent high-energy x-ray diffraction experiments were performed at room temperature and reveal an apparent phase transition during mechanical loading, consistent with previous macroscopic electrical measurements. The transition lines between the relaxor states and the stress-induced ferroelectric state were determined at constant temperatures with stress-dependent dielectric constant measurements, providing a stress-temperature phase diagram.